ANALISIS UPAYA PEMULIHAN DAN PENINGKATAN KEGIATAN OPERASIONAL BANDARA H. HASAN AROEBOESMAN ENDE PASCA PANDEMI COVID-19 - Tesa oktaviani nua; Anita Nur Masyi'ah (Jurnal Publikasi Ekonomi dan Akuntansi, 2023)
Since early March 2020, the Covid 19 pandemic has hit Indonesia and brought a major disaster to the world of aviation. This is evidenced by the drastic decrease in the number of passengers and aircraft at Ende Airport. Travel requirements and PSBB policies discourage people from traveling by air. Ende Airport's operational activities have decreased drastically due to the Covid 19 pandemic. This study aims to find out what efforts have been made to recover and increase operational activities after the Covid 19 pandemic and what obstacles have become obstacles in efforts to implement recovery and increase operational activities at H. Hasan Aroeboesman Ende after Covid-19.pandemic. The research was conducted qualitatively using primary and secondary data. Efforts to restore and increase Ende Airport operational activities after the Covid-19 pandemic are efforts originating from Ende Airport to improve and restore its airport operations after the Covid-19 pandemic. This study uses qualitative methods, obtained from primary and secondary data. Primary data is done by data, observation, interviews, and secondary data is done by documentation and literature study. This research was carried out at Ende Airport in August and September 2022. The results of this research are Ende Airport's efforts to improve and restore its post-pandemic airport operations, including: carrying out promotions, trying to create new flight routes, preparing places for rapid tests and coordinating with the local health office to administer vaccines. The obstacles that hinder this effort are the high ticket prices, the views of the public who are still worried about using air transportation services due to the Covid 19 pandemic and a lack of understanding about the requirements for people's travel by air transportation.